KETERASINGAN DALAM UTOPIA CERPEN “ANTARA DEN HAAG DAN DELFT” KARYA RILDA A.OE TANEKO - Galuh Febri Putra (POETIKA, 2014)
This paper is focused on the alienation which caused by nation in Rilda A.Oe Taneko’s short story entitled “Antara Den Haag dan Delft”. Independent nation which is simply a rewriting of what has been taken away by the colonizer created fixation of space which can not accommodate all interests. This circumstance forced ‘kakek’ (an old man) in the short story to imagine the ideal space outside the nation. However, in the utopia kakek feels alienated. This paper used the Postcolonial theory by Sara Upstone  which conceptualize that the independent nation and colonizer do the same act, they just covered the instability in the space of nation. In the attempt to achieve independence, nation used the slogan unity in diversity. The instability  led a journey to the utopia city where there is no limitations in place. Kakek in the short story feels alienated in the utopia city because of the cover of instability in the form of his love to the nation that given to him. Anything that is not a part of his nation turned into something strange.  Keywords: alienation, utopia, love to the nation.